Structured reporting of neuroendocrine tumors in PET/CT using [18F]SiTATE - impact on interdisciplinary communication - Anna Hinterberger; Lukas Trupka; Sophia Kortbein; Ricarda Ebner; Nicola Fink; Matthias F. Froelich; Dominik Nörenberg; Carmen Wängler; Björn Wängler; Ralf Schirrmacher; Adrien Holzgreve; Matthias Brendel; et al. (Scientific Reports, 2025)
Abstract Our retrospective single-center study aims to evaluate the impact of structured reporting (SR) using a self-developed template on report quality compared to free-text reporting (FTR) in [18F]SiTATE Positron Emission Tomography/Computer Tomography (PET/CT) for the primary staging and therapy monitoring of patients diagnosed with neuroendocrine tumors (NET). In total 50 patients were included. FTRs and SRs were generated post-examination. All reports were evaluated by a radiologist and a surgeon through a questionnaire to determine their contribution to facilitating clinical decision-making and to assess their completeness, linguistic quality, and overall quality. SR significantly increased the capacity of facilitating therapy decision-making from 32% in FTR to 55% in SR (p < 0.001). Trust in the report was significantly higher in SR with a mean of 5.0 (SD = 0.5) vs. 4.7 (SD = 0.5) for FTR (p < 0.001). SR received significantly higher mean ratings regarding linguistic quality with 4.7 for SR vs. 4.4 for FTR (p = 0.004) and overall report quality with a mean of 4.9 for SR vs. 4.6 for FTR (p < 0.001). Concluding that SR enhances the overall quality of reports in [18F]SiTATE-PET/CTs for NET staging, serving as a tool to streamline clinical decision-making and enhance interdisciplinary communication in the future.